Magnetic Resonance Spectroscopy as a tool to study the role of GABA in motor-cortical plasticity. - Stagg, C (2014)
Quantification of a number of neurochemicals within localised regions of tissue has long been possible using Magnetic Resonance Spectroscopy (MRS). In recent years, MRS has increasingly been utilised as a method to indirectly assess neuronal activity in vivo, primarily via measurement of the major neurotransmitters glutamate and γ-aminobutyric acid (GABA). To date a number of studies have highlighted relationships between local GABA levels and behaviour, and have demonstrated the modulation of GABA by protocols designed to induce synaptic plasticity. This review aims to examine the literature on MRS-assessed GABA changes in synaptic plasticity, focussing on the primary motor cortex (M1), to relate these to animal studies on the role of GABA in synaptic plasticity, and to highlight some of the important outstanding questions in interpreting MRS findings.